Investigating young adults' views about suicidal behaviour in South Africa. - Rontiris, Anastasia (My University, 2014)
Suicidal behaviour is a serious public health problem. Globally and in South Africa prevalence rates are increasing particularly amongst young adults, highlighting a need for preventative measures. One way to assist with these efforts is to enhance our understanding of suicide by investigating young adult’s views towards suicidal behaviour. To date, limited research exists in the South African context on views towards suicide. The purpose of this study was to explore young adult’s views about suicidal behaviour within the context of culture and religion. A qualitative research design was adopted using semi-structured individual interviews. The participants were ten students from the University of the Witwatersrand between the ages of twenty and twenty-five. The results were analysed using thematic content analysis. The results revealed that participants predominantly identified psychological, social and cultural risk factors for suicidal behaviour, ignoring the influence of psychopathology. The participants also highlighted the influence of the social and cultural context on shaping not only their own views, but those of their family, culture and community. The results indicated that unlike their families, religions and communities, the participants did not hold negative views towards suicide. Instead they appeared to have a great deal of sympathy towards those who had attempted or committed suicide and seemed to denounce the negative views of those around them. Lastly, the results illustrated that role of gender was central to explanations gender differences in suicidal behaviour. Implications of the findings for future research and prevention are discussed.
Keywords: Suicidal behavior--South Africa.